The evaluation of inflammatory process, endothelial dysfunction and oxidative stress in sleep apnea - Dündar, Yusuf; Çadallı TatarTatar, Emel; Saylam, Güleser; Korkmaz, Hakan; Tarık Selçuk, Ömer; Özdek, Ali; Ardıç, Sadık (ENT Updates, 2014)
Objective: To investigate the correlation of inflammatory process, endothelial dysfunction and oxidative stress with obstructive sleep apnea (OSA). Methods: In our prospective cross-sectional clinical study in a tertiary referral hospital, we evaluated 63 patients with newly diagnosed OSA and 9 simple snorers. Each patient was evaluated in terms of additional systemic diseases and laboratory tests. In addition to routine blood analysis; oxidative stress markers (leptine, RBP), vascular endothelial markers (ICAM-I, VCAM-I) and inflammatory markers (Crp, IL-6, TNF-alpha, isoprostane) were analyzed. Polysomnography test was performed and study population was divided into four groups depending on their AHI values. The levels of markers were analyzed and compared between the four groups. Results: There was a weak correlation between the isoprostane levels and mean apnea duration and also a mild correlation to the maximum apnea duration. A weak correlation was detected between leptine and VCAM levels to age and also a weak negative correlation was detected between CRP levels to age. The leptin levels were found to be mildly correlated to BMI and abdominal circumference. The ICAM levels were found to have a weak correlation to BMI and abdominal circumference. Conclusion: Our results indicate a correlation between sleep apnea and oxidative stress. These results may help to explain the association of co-morbid diseases with OSAS. Further investigators should aim to explain key steps of inflammatory response in sleep apnea.